Gut bacteria characteristic of the infant microbiota down-regulate inflammatory transcriptional responses in HT-29 cells - Pathmanathan S.G.; Lawley B.; McConnell M.; Baird M.A.; Tannock G.W. (Academic Press, 2024)
Indexed by WOS/Scopus/ERA